Servant Leadership as an enhancer of intrinsic motivation in MOOCs - Bolger, Mary (Proceedings of the International Conference on Networked Learning, 2014)
This paper proposes that a servant leadership style of engagement in a MOOC learning environment has the potential, via the implementation of a collaborative engagement model, to enhance learner intrinsic motivation. Servant Leadership is a leadership philosophy based on the premise ‘primus inter pares’ or first amongst equals, thus the leader leads from within, sharing power rather than exerting power via controlling influence and the oppression of others. This style of engagement results in personal growth, enhanced identity and strengthening of community. Traditional concepts of learning, understood in terms of engagement with resources, tutor and others have become complex endeavours, with varying pedagogies emerging over time in alignment with the changes in the resources, context and number of people involved in the teaching and learning process. Nowadays technology is dominating as a mediator between learner and learning with the role of ‘other(s)’ in one’s learning being somewhat less regulated or even diminished. Technology based tools require, amongst other things, well developed capabilities in self directed learning strategies. Self directed learning implies taking a certain responsibility for one’s own learning journey, often depicted in blogs, wikis and e-portfolios. However, many users of technology are not confident users of tools that are implicit in models of self directed learning in virtual contexts like MOOCs. In such instances, the autonomy required to achieve the level of competence in self directed learning strategies is a function of the relatedness of the learner to others in the social context of learning. These aspects of learning namely, competence, relatedness and autonomy are key elements of motivation and relate to basic psychological needs of the individual. Satisfying these needs allows for optimal growth of the person. As such then, the social context can either serve to enhance or diminish motivation. It is anticipated that the inclusion of an appropriate collaborative engagement model, i.e. one based on servant leadership attributes, has the potential to engage the learner in such a way that enhances intrinsic motivation and consequently the development of the necessary self direction required in MOOC settings. We envisage that a servant leadership style of engagement mediates the relationship between collaboration and enhanced intrinsic motivation, and further that enhanced motivation will lead to greater learner competence, and autonomy and thus self direction in learning, a key prerequisite for sustenance and survival in a MOOC environment.